Pharmacological Prevention of Neonatal Opioid Withdrawal in a Pregnant Guinea Pig Model - Safa, Alireza; Lau, Allison R.; Aten, Sydney; Schilling, Karl; Bales, Karen L.; Miller, Victoria A.; Fitzgerald, Julie; Chen, Min; Hill, Kasey; Dzwigalski, Kyle; Obrietan, Karl; Phelps, Mitch A.; et al. (Frontiers in Pharmacology, 2021)
Newborns exposed to prenatal opioids often experience intense postnatal withdrawal after cessation of the opioid, called neonatal opioid withdrawal syndrome (NOWS), with limited pre- and postnatal therapeutic options available. In a prior study in pregnant mice we demonstrated that the peripherally selective opioid antagonist, 6beta-naltrexol (6BN), is a promising drug candidate for preventive prenatal treatment of NOWS, and a therapeutic mechanism was proposed based on preferential delivery of 6BN to fetal brain with relative exclusion from maternal brain. Here, we have developed methadone (MTD) treated pregnant guinea pigs as a physiologically more suitable model, enabling detection of robust spontaneous neonatal withdrawal. Prenatal MTD significantly aggravates two classic maternal separation stress behaviors in newborn guinea pigs: calling (vocalizing) and searching (locomotion) - natural attachment behaviors thought to be controlled by the endogenous opioid system. In addition, prenatal MTD significantly increases the levels of plasma cortisol in newborns, showing that cessation of MTD at birth engages the hypothalamic-pituitary-adrenal (HPA) axis. We find that co-administration of 6BN with MTD prevents these withdrawal symptoms in newborn pups with extreme potency (ID50 0.02 mg/kg), at doses unlikely to induce maternal or fetal withdrawal or to interfere with opioid antinociception based on many prior studies in rodents and non-human primates. Furthermore, we demonstrate a similarly high potency of 6BN in preventing opioid withdrawal in adult guinea pigs (ID50 = 0.01 mg/kg). This high potency appears to run counter to our pharmacokinetic studies showing slow 6BN transit of both the placenta and maternal blood brain barrier in guinea pigs, and calls into question the preferential delivery mechanism. Rather, it suggests a novel receptor mechanism to account for the selectively high potency of 6BN to suppress opioid dependence at all developmental stages, even in adults, as compared to its well-established low potency as a classical opioid antagonist. In conclusion, 6BN is an attractive compound for development of a preventive therapy for NOWS.